Brazillian studies in HIV-associated dementia - Pacheco Filho, José Roberto; Santos, Flávia Heloísa (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Brazilian data from 2005 shows that since 1983 were registered more than 590,000 cases of aids (acquired immunodeficiency syndrome) which is registered an infectcontagious disease caused by HIV-1 (human immunodeficiency virus). Humor alterations, opportunist infections, and neurological changes are associated with the virus action at the central nervous system. Across the diverse possible sequels of aids, neurocognitive disorders which have implication in social, ocupational, and financial activities are observed are observed, as well in adherence to the treatment; besides when they are progressive, they can be compatible to the diagnosis of HIV-associated dementia. The present article consists of a survey of articles done at Medline Pubmed related to the terms: aids, dementia, Brazil, and HIV. The results indicated that publications on this regards are scarce, since 17 articles were found and only seven really discussed specifically questions related to dementia. The conclusion is that the scientific production in this area must be amplified nationally since the subject has a huge impact in the quality of life of people with HIV/aids.